"My role as a parent, to me, it has narrowed" the impact of early inflammatory arthritis on parenting roles: a qualitative study. Issue 1 (2nd January 2023) - Codd, Yvonne; Coe, Áine; Mullan, Ronan H.; Kane, David; Stapleton, Tadhg
Abstract: Purpose: To explore the impact of early inflammatory arthritis on participation in parenting roles. Materials and methods: Twenty-four individuals (20 female) aged between 32 and 62 years with early inflammatory arthritis (<2 years duration) and who were parents of dependent children (≤21 years) were interviewed. A qualitative description study design was used, and thematic analysis methodologies were employed in the data analysis. Results: Parenting roles were significantly impacted in early disease and extensive parenting restrictions were identified regardless of age and gender. Physical symptoms hampered "everyday mammy activities." Parent-child interactions were altered by the emotional impact of early arthritis including low mood and irritability. Participants emphasised remorse at the negative impact of their arthritis on their children's childhood. Parent-role identity and parents' perception of how they were viewed by their children were negatively impacted by early disease with considerable self-imposed pressure to shield children from the consequences of arthritis. A forced "role switch" requiring relinquishing of some parenting tasks was identified as an unwanted burden associated with inflammatory arthritis. Conclusion: Inflammatory arthritis has a negative impact on parenting which is present from disease onset. Understanding factors which influence parenting with arthritis is important to identify appropriate healthcare interventions. Implications for rehabilitation: An early diagnosis of inflammatory arthritis is synonymous with considerable challenges in performing parenting tasks and activities which are present despite early medical management and drug therapy. Physical and psychosocial sequelae of early inflammatory arthritis result in restrictions in the execution of parenting activities and are accompanied by a forced "role switch". The disease impact on parenting differs in early and established inflammatory arthritis and requires distinct healthcare approaches and interventions to adequately address the needs. Parent role identity and perceived lack of control are intrinsically linked to the degree of perceived negative impact on parenting and these factors should be considered in the design and evaluation of appropriate healthcare interventions for this population.